Insect diversity and abundance during the crepuscular and nocturnal temporal periods in the Kota Gelanggi limestone complex, Pahang, Malaysia - Ting, Jin Sia; Nur Atiqah Abd Rahman,; Ng, Yong Foo; Salmah Yaakop,; Akbar Zubaid, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The diversity and abundance patterns of nocturnal insect orders during the crepuscular and nocturnal periods, 6pm-9pm, 10pm-1am and 4am-7am at Kota Gelanggi limestone complexes were investigated. The insects were collected by using light traps over a period of six months from May to October 2014. A total of 35 732 individuals from 19 orders were captured. Coleoptera (n=14 103, 39.5%), Hymenoptera (n=10 030, 28.1%) and Diptera (n=4 821, 13.5%) were the most abundant orders. The results showed a bimodal pattern in the abundance of insects where more were caught during dusk followed by dawn and the lowest during the nocturnal period. However there was no significant difference (F= 0.71, df= 2, P> 0.05) in insect abundance between the three sessions. Studies on nocturnal insect activity patterns give us an understanding of the behaviour of the insects especially agricultural pest insects, and this information is necessary to develop effective pest control management.